Multisensory Storytelling in Disability Arts: Innovations in Accessibility and Audience Engagement - Kathleen Sitter; Amber P. E. Young; Ana Herrera; Heath Birkholz; Alison L. Grittner (Studies in Social Justice)
Fractured Time: Sensory Dimensions of the Pandemic is a multisensory four-dimensional installation created by neurodivergent artists. The piece communicates aspects of the artists’ lived experiences of the pandemic through the sensory modalities of touch, sound, smell, and sight. In this paper, the authors consider the installation of Fractured Time at three distinct, non-traditional sites. Reproducing the installation at each site presented unique complications for accessibility, therefore requiring adaptation where possible. These experiences provide a foundation for discussing Disability Arts. By addressing the questions, how might we engage sensory modalities without ocularcentrism overpowering the storytelling process?, and what are the ways we can address accessibility in curating an art installation?, the authors propose three creative phases when considering accessible curation: isolate (falsely), instruct, and imagine. These steps are explained within the context of the installation.